A way forward with eco evo devo: an extended theory of resource polymorphism with postglacial fishes as model systems. (19th June 2019) - Skúlason, Skúli; Parsons, Kevin J.; Svanbäck, Richard; Räsänen, Katja; Ferguson, Moira M.; Adams, Colin E.; Amundsen, Per‐Arne; Bartels, Pia; Bean, Colin W.; Boughman, Janette W.; Englund, Göran; Guðbrandsson, Jóhannes; et al.
ABSTRACT: A major goal of evolutionary science is to understand how biological diversity is generated and altered. Despite considerable advances, we still have limited insight into how phenotypic variation arises and is sorted by natural selection. Here we argue that an integrated view, which merges ecology, evolution and developmental biology (eco evo devo) on an equal footing, is needed to understand the multifaceted role of the environment in simultaneously determining the development of the phenotype and the nature of the selective environment, and how organisms in turn affect the environment through eco evo and eco devo feedbacks. To illustrate the usefulness of an integrated eco evo devo perspective, we connect it with the theory of resource polymorphism (i.e. the phenotypic and genetic diversification that occurs in response to variation in available resources). In so doing, we highlight fishes from recently glaciated freshwater systems as exceptionally well‐suited model systems for testing predictions of an eco evo devo framework in studies of diversification. Studies on these fishes show that intraspecific diversity can evolve rapidly, and that this process is jointly facilitated by ( i ) the availability of diverse environments promoting divergent natural selection; ( ii ) dynamic developmental processes sensitive to environmental and genetic signals; and ( iii ) eco evo and eco devo feedbacks influencing the selective and developmental environments of the phenotype. We highlight empirical examples and present a conceptual model for the generation of resource polymorphism – emphasizing eco evo devo, and identify current gaps in knowledge.